1990
DOI: 10.1021/np50069a018
|View full text |Cite
|
Sign up to set email alerts
|

ent-Kauranoid Diterpenes from Artemisia sacrorum

Abstract: A new ent-kauranoid diterpene diglycoside has been isolated from Artemisia sacrorum along with two known ent-kauranoid diterpenes. Their structures are elucidated by means of nmr analysis (DEPT, 1H-1H COSY, 1H-13C COSY, and 1H-1H decoupling).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…From the aqueous extract of the aerial parts of this plant, two kaurane glycosides, 86 and 87, have been isolated [128], in addition to the kauranetriol 88.…”
Section: R' = R" = Hmentioning
confidence: 99%
“…From the aqueous extract of the aerial parts of this plant, two kaurane glycosides, 86 and 87, have been isolated [128], in addition to the kauranetriol 88.…”
Section: R' = R" = Hmentioning
confidence: 99%
“…The relative configuration of the aglycone was assigned by a ROESY experiment. Specifically, the correlations ( Figure 3) between H-C(19)/H-C (20), H-C(20)/ H ax -C (11), H-C(20)/H-C (14), and H ax -C(11)/H-C (14) indicated that these H-atoms were cofacial. The absolute configuration was established by quantum chemical ECD calculation.…”
Section: Introductionmentioning
confidence: 99%
“…The extract was then subjected to normal-phase silica gel column [2 kg, CHCl 3 -MeOH (100 : 0 → 0 : 100, v/v)] to produce eight fractions. Each fraction was subjected to further separation using repeated ODS silica gel, Sephadex LH-20 column chromatography, and HPLC to give smaditerpenic acid A (1, 60 mg), smaditerpenic acid B (2, 80 mg), smaditerpenic acid C (3, 70 mg), smaditerpenic acid D (4, 70 mg), ent-kaurane-3β,16β,17-triol (5, 20 mg), [6] ent-kaurane-16β,17-diol-19-oic acid (6, 100 mg), [7] ent-kaurane-16β,17,18-triol (7, 30 mg), [8] 1-pentacosanol (8, 80 mg), [9] and 1-octacosanol (9, 52 mg). [9] Smaditerpenic acid A (1) …”
Section: Extraction and Isolationmentioning
confidence: 99%